2005
DOI: 10.1001/jama.294.4.433
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Prostate Cancer–Specific Mortality Following Biochemical Recurrence After Radical Prostatectomy

Abstract: Clinical parameters (PSADT, pathological Gleason score, and time from surgery to biochemical recurrence) can help risk stratify patients for prostate cancer-specific mortality following biochemical recurrence after radical prostatectomy. These preliminary findings may serve as useful guides to patients and their physicians to identify patients at high risk for prostate cancer-specific mortality following biochemical recurrence after radical prostatectomy to enroll them in early aggressive treatment trials. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

27
744
4
14

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,238 publications
(789 citation statements)
references
References 31 publications
27
744
4
14
Order By: Relevance
“…The pGS is the best predictor of the natural history of PCa because all other variables depend on it [13,14,15,16]. We showed that serum TT was a significant preoperative variable associated with tumor grade and it ranked above PSA (tables 2, 3).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The pGS is the best predictor of the natural history of PCa because all other variables depend on it [13,14,15,16]. We showed that serum TT was a significant preoperative variable associated with tumor grade and it ranked above PSA (tables 2, 3).…”
Section: Discussionmentioning
confidence: 82%
“…It has been shown that the prostatectomy Gleason score (pGS) is the factor that best predicts biochemical recurrence, development of metastases and PCa-specific mortality since all other variables (baseline PSA, PSA doubling time, pathologic stage) depend on it [13,14,15,16]. Also, the association of pretreatment serum TT levels with pGS still remains a controversial and unsolved subject [4,6,7,10,11,12,17,18,19,20,21,22,23,24,25,26,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Il est aussi de mise en cas de récidive biologique, locale ou métastatique, et de contre-indication du traitement local à un stade localisé 1 . L'HAA réduit les niveaux sériques de la testostérone, qui passent d'un taux normal d'environ 500 à 600 ng/dl (17,(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)8 nmol) à un taux de castration. Classiquement, la castration est considérée comme efficace si le taux de testostérone a été abaissé à un seuil de 50 ng/dl (soit 1,73 nmol/l) ou à une valeur inférieure à 5 % du taux normal 2,3 .…”
Section: Introductionunclassified
“…On assiste également à une forte augmentation de l'utilisation de l'HAA pour traiter les formes localisées de cancer de la prostate 5 . La médiane de survie est de 16 ans chez les patients ayant connu une récidive après prostatectomie radicale 6 . Le taux de survie est de 80 % 10 ans après la récidive si le temps de dédoublement du PSA est égal ou supérieur à 6 mois 7 .…”
Section: Introductionunclassified
“…In fact, most patients will not develop any clinical manifestations despite having BCR. 6,18,24 Evidence suggests that adjuvant radiation therapy should be offered to high-risk patients after RP. [10][11][12][13] Critics to this approach cite that this modality was not compared to early salvage therapy in pivotal studies, as well as that more recent trials have failed to demonstrate a survival benefit.…”
Section: Discussionmentioning
confidence: 99%